2015
DOI: 10.1159/000370075
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Structural Brain Changes and NRG1 Gene Variants in First-Episode Nonaffective Psychosis

Abstract: Background: Structural brain abnormalities are already present during the early phases of psychosis, but factors underlying brain volume changes are still not well understood. The neuregulin 1 gene (NRG1), influencing neurodevelopment and neuroplasticity, has been associated with schizophrenia. Our aim was to examine whether variations in the NRG1 gene (SNP8NRG221132, SNP8NRG6221533 and SNP8NRG243177 polymorphisms) influence longitudinal changes in the brain during a first episode of psychosis (FEP). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 57 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The C 'risk' allele at this locus was associated with lower white matter volume (detected with voxel based morphometry) in the regions of the right uncinate fasciculus, right inferior longitudinal fasciculus and in the overlapping portions of the anterior thalamic radiations and the corticopontine tracts (Cannon et al 2012) compared to TT-genotype carriers. Further, less gross white matter (Suarez-Pinilla et al 2015) and longitudinal changes in lateral ventricular volumes were also noted in those with the C allele at SNP8NRG221533 (Suarez-Pinilla et al 2015). However, one European study has reported negative associations with hippocampus and lateral ventricular volumes (Dutt et al 2009) and the 'non-risk' T-allele was associated with decreased anterior cingulum fractional anisotropy compared to CC genotype carriers in a Han Chinese schizophrenia population (Wang et al 2009), suggesting HAP ICE 'risk' alleles may differ by ancestry.…”
Section: Structural Neuroimaging Studiesmentioning
confidence: 99%
“…The C 'risk' allele at this locus was associated with lower white matter volume (detected with voxel based morphometry) in the regions of the right uncinate fasciculus, right inferior longitudinal fasciculus and in the overlapping portions of the anterior thalamic radiations and the corticopontine tracts (Cannon et al 2012) compared to TT-genotype carriers. Further, less gross white matter (Suarez-Pinilla et al 2015) and longitudinal changes in lateral ventricular volumes were also noted in those with the C allele at SNP8NRG221533 (Suarez-Pinilla et al 2015). However, one European study has reported negative associations with hippocampus and lateral ventricular volumes (Dutt et al 2009) and the 'non-risk' T-allele was associated with decreased anterior cingulum fractional anisotropy compared to CC genotype carriers in a Han Chinese schizophrenia population (Wang et al 2009), suggesting HAP ICE 'risk' alleles may differ by ancestry.…”
Section: Structural Neuroimaging Studiesmentioning
confidence: 99%
“…The following evidence supports the notion that NRG1 and ErbB4 alteration contributes to pathophysiological mechanisms of SZ. First, NRG1 and ErbB4 variants have been shown to be associated with reduced volume and decreased activation of brain regions and cognitive phenotypes (37)(38)(39) and with responses to antipsychotics treatment (40)(41)(42). Second, altered NRG1 or ErbB4 levels were detected in postmortem brain samples and peripheral blood of SZ patients (43)(44)(45).…”
mentioning
confidence: 99%
“…Gender distribution ranged from 58 to 79% male, and mean AAO from 10 to 30.6 years old. Eight of the eleven studies included a healthy control (HC) group for genetic, 37 , 42 , 43 structural MRI, or both types of analysis, 34 36 , 40 , 41 , 44 and one of these studies also included a sibling comparison group. 41 …”
Section: Resultsmentioning
confidence: 99%
“…Genes examined were BDNF, 34 , 35 , 42 , 44 COMT, 41 NRG1, 36 , 40 DISC1, 38 CNR1, 37 GAD1, 39 and G72. 43 All studies genotyped individual SNPs, three studies additionally performed haplotype analysis, 39 , 40 , 43 and one study analyzed a microsatellite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation